2018
DOI: 10.1117/1.jbo.23.5.057004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing effects of pressure on tumor and normal tissue physiology using an automated self-calibrated, pressure-sensing probe for diffuse reflectance spectroscopy

Abstract: Diffuse reflectance spectroscopy (DRS) represents a quantitative, noninvasive, nondestructive means of assessing vascular oxygenation, vascularity, and structural properties. However, it is known that such measurements can be influenced by the effects of pressure, which is a major concern for reproducible and operator-independent assessment of tissues. Second, regular calibration is a necessary component of quantitative DRS to account for factors such as lamp decay and fiber bending. Without a means of reliabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…This tool requires (1) rapid feedback, (2) non-invasiveness, (3) portability, (4) a quantitative approach and (5) minimal operator bias. An instrument that meets these requirements could significantly decrease the emotional and physical toll of patients with suspicious lesions and prioritize patients with a high likelihood of malignancy by increasing clinical efficiency [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This tool requires (1) rapid feedback, (2) non-invasiveness, (3) portability, (4) a quantitative approach and (5) minimal operator bias. An instrument that meets these requirements could significantly decrease the emotional and physical toll of patients with suspicious lesions and prioritize patients with a high likelihood of malignancy by increasing clinical efficiency [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For applications in HNSCC, however, a smaller probe is better suited to obtaining functional measurements as long as it can be rigorously optimized as DRS is generally not used in combination with ultrasound, MRI or x-ray diagnostic imaging. Prior studies using DRS have found that reproducibility is improved with real-time assessment of probe pressure and system throughput calibration [ 5 ], which must be addressed before widespread clinical testing.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations